REPORTING THE DETECTION RESULT OF SARS-CoV-2 ANTIBODY RAPID TEST OF COMPANY’S EMPLOYEES IN SURABAYA AND PASURUAN, INDONESIA - Mulya Dinata; Angelina Tulus; Evelyn Ongkodjodjo; Lukas Slamet Rihadi; Dewa Ayu Liona Dewi; Gabrielle Tjipta Joewana; Nurlita Wulansari (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Coronavirus (CoV) is a large family of viruses that causes illnesses ranging from mild to severe symptoms. Coronavirus Disease (Covid-19) is a new type of virus that has never been indentified in humans before. Methods: All antibody test methods and RT-PCR tests have an optimum time window in the incubation period or infection of a person. The antibody test method cannot be used as an early detection tool for people who are still on the first day of the incubation process. IgG and IgM antibody levels are still low on the first day of infection, even though the number of viral particles is very high at the beginning. Result: Sars-Cov-2 (Covid-19) antibody examination sample was taken from Main Clinic of Sentra Medika Surabaya, from May to August 2020, with the age range of 18-65 old amounted to 1015 people. The number of samples with the age range of 40-49 is 404 people (39,90%), Production Department has 773 samples of people (76,16%), the number of security samples is 39 people (3,84%), and others have 109 samples of people (10,74%). The number of male samples is 666 people (65,62%) more than female 349 people (34,38%). Positive Covid-19 Antibody examination results for Office Department are IgM 3 people, IgG 3 people, and the total numbers are 6 people (21%). Positive Covid-19 Antibody examination results for the production department are IgM 14 people, IgG 1 person. So, the total numbers are 17 people (59%). The most positive Covid-19 antibody examination result is the production department namely 59% and including positive results for IgM and IgG. The condition above the production department has the most frequent because of the condition of employees including some companies which had overtime work or 2 shifts. Conclusion: The highest number of Positive Covid-19 antibody examination result. The most department is the production department. The age range of 50-59 years old has a small number. At the time of being infected with Covid-19, IgG and IgM are negative, it needs time to get a positive examination result of IgG or IgM or both. The antibody examination method cannot be used as an early detection tool for Covid-19.